Predicting inflation: A holistic approach - Kujtim Avdiu; Stephan Unger (Journal of Risk and Financial Management, 2022)
The quantity equation is a well-established, theoretic, long-run concept that has been criticized for a variety of reasons, i.e., that no precise statements about causality or dynamics between money growth and inflation can be inferred from its components. These shortcomings can be tackled by estimating inflation based upon a holistic approach and the performance of a ceteris paribus analysis for various levels of quantity and velocity of money, as well as GDP. By testing the validity of the quantity equation, it is possible to evaluate possible effects of elevated budget deficits, unprecedented expansions of the monetary base caused by global lockdowns, and a crash in global productivity, on inflation. The main findings of this paper suggest that the level of productivity is the main driver of inflation. The quantity and velocity of money only play a subordinate role in the determination of the inflation level. If inflation is holistically seen as a function of the quantity and velocity of money, as well as general economic productivity, the level of inflation can be very well explained by comparing the supply side with general economic productivity.
Keywords: E01; E03; E04; E05; 330; inflation; linear estimation; quantity theory of money; driver analysis